72.2k views
4 votes
Show that (2, 1) is a solution of the system of equations.

x + 3y = 5,
y = –x + 3
Substitute (2, 1) into x + 3y = 5 to get .____
Simplify the equation to get ____
Substitute (2, 1) into y = –x + 3 to get ____
Simplify the equation to get .____

2 Answers

5 votes

Answer:

1. 2 + 3(1) = 5

2. 5 = 5 is true

3. 1 = -(2) + 3

4. 1 = 1 is true

the comment guy is correct

Explanation:

User Brian Yarger
by
5.0k points
3 votes

9514 1404 393

Answer:

  • 2 + 3·1 = 5
  • 5 = 5
  • 1 = -2 +3
  • 1 = 1

Explanation:

Put the first value of the ordered pair where x is in the equation. Put the second value of the ordered pair where y is in the equation. This gives you the expressions that go in the "Substitute (2, 1) into ..." blanks.

Perform the indicated arithmetic to simplify the expression.

You will get answers that look like ...

  • 2 + 3·1 = 5
  • 5 = 5
  • 1 = -2 +3
  • 1 = 1
User Sam Benson
by
5.4k points